2018
DOI: 10.1007/s00590-018-2206-y
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of bariatric surgery on spinal epidural lipomatosis: case report and literature review

Abstract: Spinal epidural lipomatosis is an abnormal accumulation of unencapsulated epidural fat causing compression of the neural elements. It can be divided into idiopathic and secondary. Secondary is often associated with chronic steroid use and endocrinopathies. Idiopathic has been associated with obesity. We report a 48-year-old man with obesity and a history of chronic back pain who developed idiopathic spinal epidural lipomatosis diagnosed by magnetic resonance imaging, which subsequently resolved completely afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…As a whole, our case present with the literature [ 28 ] highlights an important role for nonsurgical treatment of SEL and the impact of bariatric surgery on spontaneous resolution of SEL. The aforementioned patient classified as Grade III epidural lipomatosis and has shown that the importance and benefit of the Borré classification for knowing the degree of severity of this lesion.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…As a whole, our case present with the literature [ 28 ] highlights an important role for nonsurgical treatment of SEL and the impact of bariatric surgery on spontaneous resolution of SEL. The aforementioned patient classified as Grade III epidural lipomatosis and has shown that the importance and benefit of the Borré classification for knowing the degree of severity of this lesion.…”
Section: Discussionmentioning
confidence: 76%
“…[ 5 21 25 26 27 ] There are many cases reported the resolution of SLE on losing weight either by a structured weight loss program and/or by the help of bariatric surgery. [ 23 28 ] The spontaneous accumulation of fat in the epidural space is a dynamic process and sometimes associated with an increase in the peripheral fat mass. [ 28 ] Notwithstanding, the published cases of association between the resolution of symptoms in SEL and weight reduction procedure, the precise mechanisms are not widely understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 More aggressive weight reduction methods, such as bariatric surgery and calorie-restricted diets, have also been noted to provide clinical improvement due to significant loss of epidural fat deposition. 62 Overall, weight reduction may reduce the likelihood of failed management and avoid the need for surgical intervention. 63 For patients on chronic corticosteroids, management is directed at a tapered corticosteroid reduction while ensuring adequate treatment of the underlying condition.…”
Section: Treatment and Management Introduction And Overviewmentioning
confidence: 99%